AB0727 Hip osteoporosis and vertebral fractures are associated with younger age at diagnosis of spondyloarthritis: results from the comospa study. (15th June 2017) - Derakhshan, MH; Goodson, NJ; Packham, J; Sengupta, R; Marzo-Ortega, H; Molto, A; Siebert, S; ,
Abstract : Background: Spondyloarthritis (SpA) is associated with adverse bone health outcomes. It is not known whether age at disease diagnosis is associated with osteoporosis and fracture in later life. Objectives: To examine the relationship between "younger age at SpA diagnosis" and risk of osteoporosis and fractures (vertebral and low-trauma peripheral). Methods: COMOSPA is a large global cross-sectional study comprising 3984 patients with SpA from 23 countries1. We evaluated the association between "younger age at SpA diagnosis" (categorised into 5-year blocks) and vertebral fracture, low-trauma peripheral fracture, and osteoporosis (t<-2.5 on bone densitometry) using logistic regression. Models were adjusted for age, sex, BMI, smoking, alcohol, NSAIDs, DMARDs, biologics, steroids and vitamin D level. Subgroup analysis was performed, stratified by peripheral and/or axial joint involvement. Results: Data were available for 3923 participants (64% male). Median age at SpA diagnosis was 33 (IQR 25–43) years. Younger age at SpA diagnosis was not associated with the risk of vertebral fractures in the entire cohort (OR=1.11, p =0.143) nor in the subgroup with axial SpA involvement, but was increased in those with peripheral arthritis (OR=1.26, p =0.014) indicating 26% excess risk for each 5-year younger age at time of SpA diagnosis. There was no significant association between younger age at diagnosis and the risk of low trauma peripheral fractures or spinal osteoporosis in the entire cohort or any subgroups. Younger age at SpA diagnosis was associated with higher risk of hip osteoporosis in the entire cohort (OR=1.34, p =0.004) and both subgroups. Femoral neck osteoporosis demonstrated similar associations (Table). Conclusions: Younger age of SpA diagnosis was associated with higher risk of vertebral fracture in patients with peripheral arthritis but not axial disease in this study. Lack of association with vertebral fracture and spinal osteoporosis in axial disease may reflect difficulty in detecting spinal disease and osteoporosis in the presence of spinal pain and syndesmophytes. An association between hip osteoporosis and younger age at SpA diagnosis was noted. References: Ann Rheum Dis 2016;75:1016–23. Disclosure of Interest: None declared